Modified Snakes and Ladders Game as an Alternative Educational Media for Dental Caries Prevention among Elementary School Children - Rohmah, Via Nazilatur; Hidayati, Sri; Mahirawatie, Ida Chairanna (FORIKES, 2026)
Dental caries is one of the most common oral health problems experienced by school-age children, particularly those aged 6–14 years, who are considered a vulnerable and critical age group for the development of dental caries. This study aimed to determine the difference in knowledge about dental caries before and after counseling using a modified snakes and ladders game as an educational media among students of class 3A and 3B at Wachid Hasyim 2 Elementary School, Surabaya. This study employed a quasi-experimental design with a one group pretest–posttest approach. The population consisted of all students in class 3A and 3B at Wachid Hasyim 2 Elementary School, Surabaya. A total of 44 students were selected using simple random sampling. Data were collected using a questionnaire and analyzed using the Wilcoxon test. The analysis showed a p-value < 0.05, indicating a significant difference in knowledge about dental caries before and after counseling using the modified snakes and ladders game as educational media. In conclusion, counseling using a modified snakes and ladders game is effective in improving knowledge about dental caries among elementary school students.Keywords: dental caries knowledge; snakes and ladders game media; elementary school students